Hydrogen peroxide adsorption on Fe-filled single-walled carbon nanotubes: A theoretical study - Moreno, Joaquin Lorenzo Valmoria (Animo Repository, 2009)
We investigated the adsorption of hydrogen peroxide molecules on Fe-filled single-walled carbon nanotubes (SWNTs) based on density functional theory (DFT) calculations. The adsorption possibilities for the hydrogen peroxide molecule were tested by finding the minimum energy as a function of distance of the molecule from the Fe-filled SWNT. Stable structures were obtained by optimizing the hydrogen peroxide (H2O2) as it was adsorbed on to the Fe-filled SWNT. This study may serve as an initial investigation into the possibility of Fe-filled single-walled carbon nanotubes (SWNTs) as catalyst material for the proton exchange membrane fuel cell (PEMFC). © 2009 IOP Publishing Ltd.